SISTEM PENUNJANG KEPUTUSAN PEMILIHAN KARYAWAN TERBAIK DI RESTORAN SOTO PAK J MENGGUNAKAN METODE AHP: - Grace Alfa Gulo; Niya Windy Nurhidayati; Diana Aprillia; Maruloh Maruloh (LPPM Universitas Bina Sarana Informatika, 2021)
Abstract - Restaurant leaders need an employee who can be trusted to serve guests or visitors who come to the restaurant well. Selection of the best employees is an important aspect of performance management because it produces useful information for employee administrative decisions such as promotions or training and other decisions. The best employee performance is not only selecting and assigning the right employees but it is also important for leaders to plan carefully in motivating and developing employees. So it is necessary to make a Decision Support System (DSS) by applying the Analytical Hierarchy Process (AHP) method. AHP method is a method for solving an action that is associated with the comparison of the weight of importance between factors and the comparison of several alternatives. This method will give the result of the weighting of each alternative choice according to the number of specified criteria, such as type, price, location and the alternative that has the greatest weight, which is an alternative choice that is the best employee recommendation to be chosen by the restaurant leader. Keywords : Decision Support System (DSS), Analytical Hierarchy Process (AHP), Employees, Restaurant